Voicing Female Servitude in Fiction: Charlotte Brontë, Jean Rhys, and Taha Hussein - Salem, Muhammed (AUC Knowledge Fountain, 2022)
This thesis examines the literary portrayal of the female servant in Jane Eyre by Charlotte Brontë (1816-1865), Wide Sargasso Sea by Jean Rhys (1890-1979), and The Call of the Curlew by Taha Hussein (1889-1973), within the theoretical framework of subaltern and gender studies. The study shows how three female subordinates in Victorian England, Postcolonial Caribbean Islands, in addition to Bedouin Egypt bargain while trying to dismantle their intersectional subordination within the patriarchal order. The problematic yet romanticized portrayal of governessing in Jane Eyre becomes a commoditized servitude, which requires active resistance in the postcolonial setting of Wide. As for The Call, the double standards of the tribal culture crystallize the victimhood of female servants. Drawing on Crenshaw’s intersectionality and the question of subaltern’s silence as Spivak argues and on her postcolonial interpretation of Victorian novels, this study shows that at least on the level of fiction (which is not altogether cut from its historical context) the subaltern manages to maneuver, articulate, and attain a degree of agency in these three novels. Thus, it will be argued that each female servant negotiates her domestication as an Other. The study also delves into the race/gender/class nexus of the female servant in the three texts. As such, exemplary Jane demystifies the immoral prejudice against governesses; Christophine, with her Obeah and verbal fluency, challenges colonial patriarchy, embodied by the unnamed Rochester while remaining socially independent by refusing to remarry; Amna uses implicit allurement as a revenge weapon against the unnamed engineer, and thus reorients his aspirations. Each of the three female subordinates verbally voices her rebellion at a climactic moment, as she recognizes that her respective master adds intersecting vulnerabilities to her already-disenfranchised position.